(untitled) (Annals of Medical Research, 2024)
Aim: We aim to observe the clinical outcomes of our patients with distal radius fractures treated conservatively with cast immobilization. Materials and Methods: This is a retrospective observational study of 52 (13 males and 39 females) patients with distal end radius fractures who were treated with cast immobilization.We noticed there were three different groups of patients with different periods of cast immobilization and the onset of rehabilitation.The first group (n=18) was undergone 4 weeks of cast immobilization, the second group (n=17) underwent 5 weeks, whereas the third group of patients (n=17) completed 6 weeks of cast immobilization.Wrist and affected hand rehabilitation were started soon after the discontinuation of the cast.All patients were assessed using a visual analog scale (VAS) for pain,Beck Depression Inventory (BDI) for emotional status, and the Disabilities of the Arm,Shoulder,and Hand(DASH) Score for overall hand function.All patients have also been evaluated for pain-free grip strength, and joints Range of Motion (ROM).The assessments were done right after removing the cast(pre-rehabilitation) and after completing rehabilitation(post- rehabilitation). Results: The VAS score,grip strength,BDI,and DASH scores showed significant differences among all groups before rehabilitation(p<0.01).The ROM and the grip strength were found to be insufficient,while the BDI and DASH scores were not significantly improved with long-term immobilization when compared to short-term immobilization.All scores showed a statistically significant difference in all groups after the 6th month (p<0.01). Conclusion: Short-term immobilization is a more effective functional outcomes and safer treatment modality before and after rehabilitation compared to long-term immobilization in the conservative treatment of distal radius fractures.